Good Governance and Sustainable Development Index in Indonesia: Panel Data Evidence from 34 Provinces - Nabila, Siti Nur Rahma; Suseno, Deky Aji (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This study examines the influence of good governance indicators, including corruption, democracy, law enforcement, and budget realization, on sustainable development in Indonesia. The research covers 34 provinces during the period 2020–2023. A quantitative approach was employed using a fixed-effects panel regression model. The findings indicate that the number of corruption cases has a significant positive effect on sustainable development, while democracy shows a positive but statistically insignificant relationship. In contrast, law enforcement, measured by the completion rate of criminal cases, and budget realization, both demonstrate significant negative effects on sustainable development. These results provide empirical grounds for designing adaptive and integrative policies that emphasize preventive measures, institutional innovation, and environmental incentives to achieve sustainability goals effectively. This study is limited by its short observation period, bias from the use of secondary data, limited variables, and a purely quantitative approach. Therefore, further research needs to extend the period, enrich the variables, and integrate mixed methods.